KARATERISTIK CAMPURAN TANAH LEMPUNG MERAH DENGAN SERBUK BATU BATA PADA BERBAGAI PORSI CAMPURAN UNTUK PENINGKATAN DAYA DUKUNG LAPISAN TANAH DASAR (SUBGRADE) - Wahjoedi, Wahjoedi; Suparman, Suparman; Supardjo, Supardjo; Suwanto, Bodja; Mulyono, Tedjo (Politeknik Negeri Semarang, 2015)
The development of increasingly advanced and sophisticated technology especially in terms of automotive technology very rapidly, in addition to models and forms of transport are designed and made with the size of economy class as well as personal, jugaringan and affordable by almost all sections of society. Besides, the welfare of society has been developing quite well, as well as the policy of the system sales of vehicles, both cars and montor that makes it easy for enthusiasts or buyers. So no one promotion through advertising inscribed that Avanza is a car that knows all corners of Indonesia. Relating it is then for the government through relevant agencies, need to pay attention and menyediakanjalan adequate as a means for smooth transportation (traffic) as supporters of pavement, through the compaction of soil material base both without additive or with additives as fillers (filter) to improve gradation of soil particle. The use of the added material should be used from the existing materials in the location (local materials) so it will be cheaper. One of them exploit the potential of local materials (clay combustion products) such as brick dust mixed with clay for the improvement of gradation and changes in physical properties through a reduction in the value of consistency so that the results increase the carrying capacity of the subgrade with CBR testing laboratory by the equation: Unsoaked y = 2,147x + 19.76 with R2 = 0.9144, Soaked 0,6303x + y = 3,924 with R2 = 0.6519, where y = carrying CBR (%), x = percent plus brick powder material.